Giant Fibrovascular Polyp of the Oropharynx - Borges, Alexandra; Bikhazi, Henry; Wensel, Jeffrey P. (American Journal of Neuroradiology, 1999)
Summary: We describe a case of a giant fibrovascular polyp arising from the oropharynx and causing vague clinical symptoms. To our knowledge, this is the first description of an oropharyngeal fibrovascular polyp reported in the medical literature. The diagnosis was based on MR imaging findings, which showed the size and configuration of the polyp as well as the site of attachment. The patient underwent surgery, and the diagnosis was confirmed histologically.